CORRELATION BETWEEN COVERAGE OF BCG IMMUNISATION AND HEALTHY HOUSES WITH FINDINGS OF PAEDIATRIC TUBERCULOSIS - Melisa Ambarwati (Universitas Airlangga, 2019)
Background: Tuberculosis in children is still found in East Java Province at 2017 with 2,749 cases of paediatric tuberculosis. The Bacille Calmette-Guérin (BCG) immunisation coverage and healthy houses in East Java Province increase every year. Purpose: This study aims to analyse the correlation between BCG immunisation and healthy houses with paediatric tuberculosis discovery in East Java Province during 2015-17. Methods: This study is observational with a correlation study design. The population in this study were children aged 0-14 years who suffered from tuberculosis in a district or city in East Java Province in 2015-17. Sampling of this study uses aggregate data on paediatric tuberculosis discovered in children aged 0-14 years, coverage of BCG immunisation and coverage of healthy houses in districts/cities in East Java in 2015-17 found in Health Profile of East Java Province 2015-17. The variables studied were paediatric tuberculosis in children aged 0-14 years, BCG immunisation coverage and healthy house; the analysis techniques were the Kolmogorov-Smirnov normality test and Pearson correlation. Results: This study shows that there is correlation between BCG immunisation and paediatric tuberculosis (p = 0.01, p <0.05) with a correlation value of 0.67, indicating a strong and positive correlation. The results also show that there is a correlation between healthy houses and children with tuberculosis (p = 0.01, p <0.05) with a correlation value of 0.63, indicating a strong and positive correlation. Conclusion: BCG immunisation coverage and healthy houses are positively correlated with paediatric tuberculosis discovered in East Java district/city.